Reformar el Título V del Segundo Libro del Código de la Niñéz y Adolescencia, en el Régimen de Alimentos, por Cuanto la Responsabilidad Subsidiaria de los Familiares del Demandado Prevista en Dicho Capítulo es Ilegal de Inconstitucional, asó como la Tabla de Pensiones Fijadas - Barrera Bravo, Álvaro Andrés (2016)
This thesis is developed within the family law, specifically as regards the subsidiary responsibility in children and adolescents, whose legal effects highlight the incongruity and inconsistency between the material and the provisions of the Constitution of the Republic. Although the principle of the best interests of the child is hierarchical application, the Constitution establishes the principle of legal certainty which guarantees the defendant the right family to not be sued or alternatively by not committed or made known to them, so coligiéndose determined by the Civil Code as to the Bonds generally. This thesis is precisely this legal impasse between the Constitution and the Code on Children and Adolescents, and the Law Amending the Resolution issued by the National Council for Childhood and Adolescence regarding Alimony Table. Therefore, the legal analysis in this thesis and the proposed legal reform , support the principle of legal certainty in accordance with the supremacy of the Constitution , without prejudice to the right of the defendant's family as his parents and siblings not alternatively be sued in court for not having food direct obligation and nor have the facts. This claim that the present work is to become a working tool and a reference guide for students of the School of Law at the National University of Loja.